Aquatic ecosystems : conservation, restoration, and management - Ramachandra, T. V.; Ahalya N.; Rajasekara Murthy, C.; Indian Institute of Science, Bangalore; International Symposium--Conservation, Restoration, and Management of Aquatic Ecosystems (2002 : Indian Institute of Science, Bangalore) (New Delhi : Capital Pub. Co., 2005)
Contributed articles presented at the Symposium--Conservation, Restoration, and Management of Aquatic Ecosystems on 9-13, December 2002 at Indian Institute of Science, Bangalore
Includes bibliographical references and index
Keywords: Aquatic ecology -- India; Aquatic ecology; Ecosystem management